1998
DOI: 10.3141/1611-07
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Weak Clay with Strong Sand and Geogrid at Sand-Clay Interface

Abstract: The load-bearing capacity of a weak clay subgrade can be increased by placing a strong granular base course of limited thickness on top of the clay layer. The load-bearing capacity can be increased further, or the thickness of the granular base course can be reduced, by separating both layers by a geogrid. Laboratory model test results for the ultimate bearing capacity of a rigid strip loading on the surface of a granular soil underlain by a soft clay with a layer of geogrid at the interface of the two soils a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…A little is known about the deformation of two-layer reinforced soil systems under repeated loading (Das et al, 1998). The most common design approach to this problem is based on the empirical formulae.…”
Section: Discussionmentioning
confidence: 99%
“…A little is known about the deformation of two-layer reinforced soil systems under repeated loading (Das et al, 1998). The most common design approach to this problem is based on the empirical formulae.…”
Section: Discussionmentioning
confidence: 99%
“…The first systematic study to improve the bearing capacity of strip footing by using metallic strip was by Binquet and Lee [1,2]. After Binquet and Lee's work, several studies have been conducted on the improvement of load bearing capacity of shallow foundations supported by sand reinforced with various reinforcing materials such as geogrids [3][4][5][6][7][8][9], geotextile [10][11][12], fibers [13,14], metal strips [15,16], and geocell [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…The ratio of improvement in the bearing capacity can be expressed in a nondimensional form as bearing capacity ratio (BCR) which is the ratio of bearing capacity of reinforced soil to bearing capacity of unreinforced soil. Several studies [5,6,26] show the effect of various parameters (e.g., / , ℎ/ , / , and / ), types of geosynthetic materials (e.g., geogrid, geotextiles, and geocell), effects of footing width ( ), types of soils, layer of soils, and so forth. But no studies are available on silty clay soil of Carbondale, Illinois, related to the improvement in bearing capacity of rectangular footing by placing sand layer on top of silty clay soil (i.e., two-layered soil) and geogrid system.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental results indicated that 20% sand with clay admixture adequately improved the properties of existing active clay for construction of highway embankments. In a similar study by Braja et al, the load-bearing capacity of a weak clay subgrade was increased by a strong granular base course on top of the weak clay layer (15). The optimal thickness of the granular soil layer with varying cyclic loading of low frequency and permanent settlement was studied.…”
mentioning
confidence: 98%
“…Mechanical stabilization of soft soils with sand has been adopted by many researchers (14,15). Sand, which is widely available, can be easily transported to the construction site and mixed with base materials according to specifications.…”
mentioning
confidence: 99%